The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ca.22867
|View full text |Cite
|
Sign up to set email alerts
|

Survey of body donation programs in the US concerning the use of donor personal information with medical students

Abstract: Body donor programs need to balance ethical concerns and educational needs. Among donor programs in the US, there is variability in the amount of donor personal information that is provided to medical students. This study assesses this variability and investigates the reasons for the variability among donor programs. Telephone interviews and email surveys were used to collect information concerning the provision and use of donor personal information with medical students. One hundred fifty-one donor programs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…Questionnaire data showed a variable use of donor personal information. Gerwer and Gest () gathered comparable survey data on US body donor programs. Most frequently (89%), the donor's cause of death was disclosed to the students, but only 19% of the programs provided them with detailed medical histories.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Questionnaire data showed a variable use of donor personal information. Gerwer and Gest () gathered comparable survey data on US body donor programs. Most frequently (89%), the donor's cause of death was disclosed to the students, but only 19% of the programs provided them with detailed medical histories.…”
Section: Discussioncontrasting
confidence: 83%
“…Moreover, students are presumably more open to innovations, and their judgments more likely led by their personal short‐term desires, like curiosity. Gerwer and Gest () also presumed that students had not actively requested more personal donor information (41%) because of a failure of communication. Therefore, anatomy departments might not be aware of students' interest in receiving more donor information.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is taught and stressed to students during education in the classroom and clinic; in contrast, participants in the anatomy laboratory often refer to a table number, student‐developed name, faculty‐developed name, living name, or no name at all to identify the cadaver students will learn from. It has been suggested that anatomy students might benefit from knowing personal information about the cadavers in the anatomy laboratory to foster a positive relationship between students and their “first patient” (Granger, ; Escobar‐Poni and Poni, ; Bohl et al, ; Talarico, ; Gerwer and Gest, ), but there has been little agreement about what types of donor information should be shared. Assessing the information that anatomy faculty currently receive about the cadavers with whom they teach, and which portion of this information those instructors share with their students, is a first step toward determining what information could be shared or should be shared.…”
Section: Introductionmentioning
confidence: 99%
“…Naming cadavers in the anatomy laboratory varies across the globe (Williams et al, ; Gerwer and Gest, ; Jones and King, ; Hasselblatt et al, ). Traditionally, anonymity and privacy are high concerns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation